THE FACTORS OF BUSINESS EFFICACY OF THE FOOD MARKET AND THEIR CORRELATION TO THE MARKETING IN FARMERS - Ivanović, Miroljub; Ćosić, Milivoje (Economics of Agriculture, 2023)
The relevant research subjecs of this study are the contemporary models of economic studies, the factors of business efficacy of the food market, and the marketing of farmers. The aim of this transversal study was to define the latent structures of business efficacy and their linear correlation with the marketing of agricultural food farmers. The pertinent sample included (N =156) male farmers from Kolubara district, Serbia. The average age of participants was 44.26 ± =10.35). The questionnaire regarding farmer’s entrepreneurial success in food production was used in this research. The values of the Cronbach’s alpha (α) coefficient of internal consistency were higher than 0.70, which means that the variables used in this research possess satisfactory psychometric criteria. Four components were extracted by analyzing the exploratory factorial analysis, with Kaiser– Guttman criterion, and the oblimin rotation of the variables. The extracted four-factor groups of latent dimensions, on the level of statistical conclusion of 0,01, were interpreted as: quality – FI, economic privilege – FII, social privilege – FIII, and competition – FIV, which together account for 68.26% of the variance. The obtained findings on the coefficient of internal consistency (Cronbach’s) confirmed the reliability and validity of the applied measuring instrument, and thus future longitudinal studies can use it for examining the farmer population in Serbia.